Surface modification of coral skeleton derived nanohydroxyapatite using polymers and its in-vitro studies for bone substitute applications. (April 2023) - Sindhya, A.; Johnson Jeyakumar, S.; Jothibas, M.; Pugalendhi, P.; Vigneshwaran, B.
Abstract: Reprocessing waste things into a functional product gives two-edged benefits, an eco-friendly environment and waste management. Nowadays, Ceramic materials based on calcium phosphates, which include Nanohydroxyapatite (nHAp) and Tri-calcium Phosphates (TCP) were extensively used in biomedical applications for their outstanding biocompatibility and bioactivity properties. In this work, nHAp (pure) and its polymeric composites were prepared through the precipitation method using the coral skeleton as a calcium precursor. Besides, to change the surface functional characteristics, the polymers were utilized as a capping agent. The synthesized samples were examined by spectrographic tools such as XRD, FT-IR, SEM/EDAX, TG-DTA, XPS and HR-TEM to find the phase, functional groups, size, morphology and thermal stability together with phase transition as well as bonding types which present in the prepared samples respectively. In addition, Simulated Body Fluid (SBF) analysis, antimicrobial assay and hemolytic test were intended to test the apatite-forming ability, antimicrobial effectiveness and hemocompatibility of the prepared samples. Therefore, the present findings suggest the possibility of developing novel HAp polymeric nanocomposites that exhibit improved biocompatible, osteoconductive which impersonates the structure of natural human bone. So, that can use for making bone and dental implants using corals skeleton as a precursor at a lesser cost. Highlights: Fabrication of Pure and Polymer Mediated Nanohydroxyapatite from Favia Pallida Coral Skeleton. First to report, polymer mediated Nanohydroxyapatite (with 2 different polymers) using the coral skeleton as a precursor. This method is free from dangerous chemicals and harmful by-products. Possible to obtain Hydroxyapatite nanocomposites with better quality with cost-effectiveness.